2023
DOI: 10.3389/fcimb.2023.1138232
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of connexin landscape fosters fast gap junction intercellular communication in human papillomavirus-infected epithelia

Abstract: Human papillomaviruses (HPVs) are highly prevalent commensal viruses that require epithelial stratification to complete their replicative cycle. While HPV infections are most often asymptomatic, certain HPV types can cause lesions, that are usually benign. In rare cases, these infections may progress to non-replicative viral cycles associated with high HPV oncogene expression promoting cell transformation, and eventually cancer when not cleared by host responses. While the consequences of HPV-induced transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
(111 reference statements)
0
3
0
Order By: Relevance
“…99 Additionally, a recent study found that in a complex epithelial model, human papillomavirus infection reduced Cx43 protein and increased both protein expression of Cx45 and localization at the cell membrane, and this resulted in an increase of GJIC. 100 While changes to connexin phosphorylation caused by acute viral infection are most commonly studied in the context of cancer biology, clearly such changes to gap junction phosphorylation will also impact cardiomyocyte coupling across a variety of viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…99 Additionally, a recent study found that in a complex epithelial model, human papillomavirus infection reduced Cx43 protein and increased both protein expression of Cx45 and localization at the cell membrane, and this resulted in an increase of GJIC. 100 While changes to connexin phosphorylation caused by acute viral infection are most commonly studied in the context of cancer biology, clearly such changes to gap junction phosphorylation will also impact cardiomyocyte coupling across a variety of viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, rather than using GJs as a mode of transfer, many oncogenic viruses including human papillomavirus (HPV), simian virus 40 (SV40) and avian sarcoma virus impair GJIC mainly by decreasing expression levels [ 252 , 253 , 254 , 255 , 256 ], altering trafficking and recycling to the membrane [ 257 ] of connexin-43 (Cx43). This effect is in accord with the fact that cancerous cells often lose their ability to communicate via GJIC [ 1 ].…”
Section: Transfer Of Viral Particlesmentioning
confidence: 99%
“…Adenoviruses push cells into S phase via E1A, E1B, and E4 protein interaction with host mechanisms, and this is required for viral replication [110][111][112] . Cardiomyocytes, themselves, are typically quiescent several days after birth, and therefore, are particularly recalcitrant to entering the cell cycle 113 . We must also now consider how activation of these signaling pathways shuts down gap junction intercellular communication in addition to facilitating S-phase entry.…”
Section: Human Adenovirus Type-5 Increases Cx43 Ser368 Phosphorylatio...mentioning
confidence: 99%